Transformation behavior and its effect on damping capacity in Fe-Mn based alloys - Jee, KK; Jang, WY; Baik, SH; Shin, MC; Choi, CS (EDITIONS PHYSIQUE, 1995)
gamma-epsilon transformation behavior in a Fe-21Mn alloy with different grain size and a Fe-32Mn-6Si alloy with various degrees of cold rolling is investigated and correlated with damping capacity. Effect of microstructure on damping capacity is discussed on the assumption that the capacity is proportional to volume swept by gamma/epsilon boundaries.
Keywords: MEMORY